Pemberian ASI Eksklusif dan M-PASI terhadap kejadian stunting - Ningtyas, Septi Fitrah; Mudhawaroh, Mudhawaroh; Bherty, Chanda Paramitha; Prihartanti, Niken Grah; Purwanti, Rosa (Puslitbang Sinergis Asa Professional, 2023)
Children with stunting are more susceptible to infectious diseases, and prolonged malnutrition can hinder their physical and mental development. Insufficient nutrition in toddlers, especially optimal nutrition such as breastfeeding (ASI), is one of the risk factors for stunting in children. The prevalence of stunting might be influenced by the provision of breastfeeding. The objective of this study is to determine the comparison of stunting incidence in the Denanyar Village, Jombang Regency, between mothers who provide exclusive breastfeeding and those using additional methods. This research employs a cross-sectional research strategy for correlation analysis. Mothers with children aged between 6 and 36 months in Denanyar Village constitute the entire population. Forty women in Denanyar Village with children aged between six and thirty-six months were selected using cluster random sampling. Data collection tools were based on surveys. Statistical tests used the Chi-Square format. The research results show a relationship between exclusive breastfeeding and complementary feeding (MP-ASI) with the incidence of stunting in Denanyar Village, Jombang Regency, with a value of p = 0.000, p < α, α=0.05. The provision of exclusive breastfeeding and appropriate complementary feeding can enhance the intelligence of the future generation and support the optimal growth and development of children.